Biomarkers of Inflammation Correlate With Clinical Scoring Indices in Human Immunodeficiency Virus–Infected Kenyans. (27th August 2018) - Letizia, Andrew; Eller, Michael A; Polyak, Christina; Eller, Leigh Anne; Creegan, Matthew; Dawson, Peter; Bryant, Christopher; D, Kim; Crowell, Trevor A; Lombardi, Kara; Rono, Eric; Robb, Merlin L; et al.
Abstract : Differences in biomarker levels exist between well-controlled HIV-infected participants on antiretroviral therapy and uninfected controls in Kenyans. Some biomarkers are correlated to scoring indices predictive of morbidity and mortality. These biomarkers could serve as prognostic indicators and inform therapeutic development. Abstract: Background: In high-income countries, inflammation has been associated with increased morbidity and mortality in human immunodeficiency virus (HIV)–infected individuals despite treatment with antiretroviral therapy (ART). However, these findings may not be generalizable to low-income settings. Methods: In this cross-sectional study, multivariable linear regression was used to compare 28 inflammatory biomarker levels in HIV-infected and -uninfected participants. Correlations between biomarkers and Veterans Aging Cohort Study (VACS) index, Fibrosis-4 (FIB-4) score, and Framingham risk score were assessed. Results: Plasma samples from 304 Kenyans were analyzed. Compared to HIV-uninfected controls, virologically suppressed HIV-infected participants had higher levels of CCL5, CXCL10, fatty acid binding protein (FABP) 2, fas ligand (FASLG), matrix metalloproteinase (MMP) 1, MMP7, soluble CD14 (sCD14), and soluble CD163 (sCD163) and lower MMP9 ( P < .01). CD4 + /HLA-DR + CD38 + (ρ = 0.32; P < .001), sCD14 (ρ = 0.25; P = .004), and sCD163 (ρ = 0.24; P = .006) were correlated with the VACS index. FABP2 was positively correlated (ρ = 0.29; P = .002), whereas MMP1 (ρ = –.32; P < .001) and MMP2 (ρ = –0.28; P = .002) were inversely correlated with the FIB-4 score. Conclusions: Differences in biomarker levels exist between well-controlled HIV-infected participants on ART and uninfected controls. Some biomarkers are correlated to scoring indices predictive of morbidity and mortality. These biomarkers could serve as prognostic indicators and inform therapeutic development.